KECERDASAN BUDAYA DAN PENYESUAIAN LINTAS BUDAYA PADA EXPATRIATE - Nur Faliza; Effan Fahrizal (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Economic globalization has made companies become multinational , public and workforce with multi- cultural backgrounds . Its important for individual have of capital competency ( knowledge and skills) to face the challenges of globalization by learning a cross-cultural adjustment for global worker, cultural intelligence can explain how individuals have capability to adaptation to multi- cultural environment . This article purpose to conceptual describe the relationship between the cultural intelligence and cross-cultural adjustment related to worker in a global culture or cross-cultural.